2013
DOI: 10.7314/apjcp.2013.14.12.7719
|View full text |Cite
|
Sign up to set email alerts
|

siRNA-mediated Silencing of Survivin Inhibits Proliferation and Enhances Etoposide Chemosensitivity in Acute Myeloid Leukemia Cells

Abstract: Background: Overexpression of survivin, a known inhibitor of apoptosis, is associated with tumor progression and drug resistance in numerous malignancies, including leukemias. The aim of this study was to investigate the effect of a specific survivin small interference RNA (siRNA) on proliferation and the sensitivity of HL-60 acute myeloid leukemia (AML) cells to the chemotherapeutic drug etoposide. Materials and Methods: The cells were transfected with siRNAs using Lipofectamine™2000 transfection reagent. Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 33 publications
(41 reference statements)
1
21
0
1
Order By: Relevance
“…Hematologic malignancies are a common disease in Asian Pacific areas (Feng et al, 2013;Jiang et al, 2013;Karami et al, 2013;Khodabandehloo et al, 2013;Kooshyar et al, 2013;Li et al, 2013;Liu et al, 2013;Ozbas-Gerceker et al, 2013;Qin et al, 2013;Shan et al, 2013). As our present study confirmed, the level of serum ferritin of patients with hematologic malignancies was significantly increased.…”
Section: Discussionsupporting
confidence: 78%
“…Hematologic malignancies are a common disease in Asian Pacific areas (Feng et al, 2013;Jiang et al, 2013;Karami et al, 2013;Khodabandehloo et al, 2013;Kooshyar et al, 2013;Li et al, 2013;Liu et al, 2013;Ozbas-Gerceker et al, 2013;Qin et al, 2013;Shan et al, 2013). As our present study confirmed, the level of serum ferritin of patients with hematologic malignancies was significantly increased.…”
Section: Discussionsupporting
confidence: 78%
“…In similar study, Karami et al showed specific silencing of survivin expression by siRNA enhanced sensitivity of leukemic cells to etoposide. 29,30 In other studies, they showed MDR1 down-regulation synergistically increased the cytotoxic effects of oxaliplatin and etoposide on oxaliplatin resistant SW480 and etoposide resistant HL-60 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Survivin is the smallest member of the inhibitor of apoptosis protein family with cell periodicity and is expressed only in G2/M phase (Kitamura et al, 2006;Srivastava et al, 2012). Survivin BIR function by binding with mitotic microtubules influences the activity of Caspase-3 of most downstream effector molecule during apoptosis and inhibition of apoptosis (Wand et al, 2004;Karami et al, 2013). Increased expression of survivin is associated with the occurrence and development of cervical cancer and is expected to become a molecular marker for early diagnosis and prognosis in cervical cancer (Lu et al, 2010;Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%